Peran Trait Mindfulness Dalam Melindungi Kesehatan Mental Mahasiswa Yang Sedang Menjalani Pembelajaran Daring - Adichandra, Alfin (Universitas Muhammadiyah Metro, 2023)
Mental health is important for the success and livelihood of college students. Studies show that college student undergoing online learning has poor mental health. Trait mindfulness has been shown to improve mental health. However, there hasn’t been any study examining the effect of trait mindfulness on mental health in college students currently undergoing online learning. This study attempts to examine whether trait mindfulness affects the mental health of college students undergoing online learning. A quantitative study was done using 122 college students undergoing online learning as participants recruited using the accidental sampling technique. This study uses Mental Health Continuum- Short Form (MHC-SF) and Mindful Attention Awareness Scale (MAAS). Data analysis was done using simple linear regression in IBM SPSS v23. The analysis revealed trait mindfulness improved the mental health of the participants. This proved that trait mindfulness effect on mental health also applied to college students currently undergoing online learning.